Perencanaan Dakwah Dalam Membentuk Karakter Religius Anak Pada Panti Asuhan Putera Muhammadiyah Medan - Nurul Hasanah; Soiman (Kartika: Jurnal Studi Keislaman, 2026)
Da'wah planning is one of the functions of da'wah management that plays a role in planning, implementing, and evaluating da'wah activities so that the goals of fostering can be achieved effectively. This study aims to analyze the application of da'wah planning in shaping the religious character of children at the Muhammadiyah Men's Orphanage in Medan. The study used a qualitative approach with a descriptive research type. Data were obtained through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results of the study indicate that da'wah planning is implemented through the stages of planning, program preparation, implementation, and evaluation. The fostering program includes tahsin, tahfidz, recitation of the Koran, kultum (sermons), adhan (call to prayer), and congregational prayer which are arranged according to the needs of the foster children. The implementation of activities is supported by the active role of the administrators, caregivers, and the religious environment of the orphanage, while obstacles faced come from differences in character, background, and psychological condition of the children. This study shows that da'wah planning has a positive impact on the formation of children's religious character, which is seen from increased discipline in worship, the ability to read the Qur'an, responsibility, independence, and self-confidence. Thus, da'wah planning is a crucial factor in fostering the religious character of children in orphanages